Using mathematical thinking approach to enhance problem solving skills in primary school - Tan, See Yee (2021)
In mathematics education, problem-solving is one of the important skills that students need to be possessed in 21st century so that they are able to encounter with the daily life challenges. However, previous studies revealed that many primary students are unable to answer the problem-solving question and they are unable to perform mathematical thinking in the problem-solving process. The aim of this study is to determine the effectiveness of using mathematical thinking approach to enhance the problem-solving skills among the primary school students and also to determine the type of mathematical thinking process that is dominant by the students after receiving the mathematical thinking lesson. An experimental design of the quantitative research was employed in this study. There were 65 participants of primary four students who were divided into control group and treatment group were selected by using the purposive sampling. The control group consists of 30 students while the treatment group consists of 35 students. The instruments used in this study was the problem-solving question of pre-test and post-test. Statistical analysis using SPSS software was used in this study to analyse the test results of pre-test and post-test. The statistical analysis results showed that there is a significant different between the pre- test and post-test of treatment group. This showed that the using of mathematical thinking approach in mathematics teaching process enhances the students’ problem- solving skills. Furthermore, repeated measure ANOVA was used to determine the type of mathematical thinking process dominant by the students. Based on the analysis results, it was found that the conjecturing process is dominant by the students while many students are still weak in generalising process. This study provides information about students’ thinking process in learning mathematics for teachers to improve students’ problem-solving skills.